Evaluating User Interaction Efficiency Using the First Click Method: Case Study on a Honey Seller SME Website - Niswatin Hasanah; Ery Setiyawan Jullev A; Budi Prasetyo; Nur Kholis (Jurnal Krisnadana, 2025)
This paper evaluates the usability of an e-commerce platform developed to empower micro, small, and medium-sized enterprises (MSMEs) in marketing and selling honey products online. A total of 50 participants—equally divided between novice and proficient users—were engaged in structured usability testing comprising task completion, performance measurement, and first-click analysis. The results indicate that the platform performs effectively in product search accuracy, information clarity, navigational intuitiveness, and perceived trustworthiness. Overall user satisfaction was high, with participants demonstrating a strong intention to reuse the platform, reflecting positive user acceptance. Nevertheless, usability challenges were observed in transaction-related operations, particularly in adding items to the cart and completing the checkout process. Quantitatively, 70% of beginners and 90% of proficient users reported challenges due to the number of required fields and perceived procedural complexity. Interface simplicity also received mixed evaluations, with beginners rating it at 70% compared to 100% among proficient users. This disparity highlights that although advanced users adapt quickly, novice users experience barriers that may discourage them from completing transactions. These findings are consistent with prior usability research emphasizing that users’ initial interactions with transaction-critical elements strongly influence trust, confidence, and willingness to continue using a platform.To address these limitations, this study proposes targeted design improvements, including enhanced cart visibility, a streamlined checkout flow, and the integration of contextual assistance features. The proposed enhancements aim to increase inclusivity, operational efficiency, and user satisfaction, thereby strengthening MSME digital adoption and competitiveness in online marketplaces.